Tile: Construction of a specific nanoprobe for scavenging ROS in hypobaric hypoxia induced brain injury of mice - Xiaobo Wang; Fuhan Fan; Ya Hou; Xianli Meng (Heliyon)
The prevention and treatment of hypobaric hypoxia brain injury (HHBI) remains an unprecedented challenge due to the complex oxidative stress response at the damage site. In this study, RuCO phthalocyanine compound (RuPc) and bovine serum albumin (BSA) were self-assembled to obtain RuPc-BSA nanoparticles for HHBI therapy. As a nanoprobe carrying and storing carbon monoxide (CO), RuPc-BSA delivers CO to pathologically damaged areas of the brain. CO specifically attaches itself to the heme functional groups on mitochondria and restricts the source of reactive oxygen species (ROS) generation. RuPc-BSA nanoparticles have been demonstrated in vitro to exhibit amazing stability as well as remarkable scavenging activity on hydroxyl radical, superoxide anion, and hydrogen peroxide. In vivo experiments showed that ROS levels in the brain of HHBI rats pretreated with RuPc-BSA decreased significantly, and neuronal function and oxidative stress levels were alleviated. Western blot and qRT-RCR results indicated that RuPc-BSA restricted the protein levels of Keap1, whereas enhanced the gene and protein levels of Nrf2. This study demonstrated that RuPc-BSA can ameliorate HHBI of mice by scavenging ROS partly via activating Keap1/Nrf2 signaling pathway.